Needs and Expectations of Long-Term Cancer Survivors: Multi-Centre Study Protocol. - Zamudio-Sánchez, Antonio; Camarero-Gómez, Pilar; Rodríguez-Manjón, Estefanía; Iglesias-Parra, María Rosa; Gómez-Salgado, Juan; Romero-Ruiz, Adolfo (MDPI, 2024)
Cancer is a social issue as its outreach affects not only mortality (it is the second cause of death in our environment) but also the costs due to morbidity and the distress it causes, as well as the losses and consequences in personal, family, work, and even social areas. This study is trying to find out the health needs of long-term cancer survivors and their perceptions and expectations of the care they received during their survival stage. For this, a joint, cross-sectional descriptive study with a qualitative and quantitative approach has been designed. For the qualitative approach, we have used different focus groups representing different geographical areas of the Spanish territory. For the qualitative approach, we have used a validated questionnaire. This study will provide a better knowledge of the quality of life of these patients, as well as their level of unmet and even unexpressed needs, in order to develop effective strategies and interventions that allow for the implementation of adapted care plans that include such unexpressed needs. This study will also allow for the creation and development of assessment methods for health results from the patient's perspective and experience. These issues require a multidisciplinary, complex approach. These survivors may require not well-known health services, as the number of these patients has grown recently, and their survival time is also longer. This research explores a wider and more thorough perspective of long-term cancer survivors' needs, experiences, and expectations to be achieved.
Keywords: Cáncer - Cuidados de enfermería; Enfermos de cáncer - Asistencia sanitaria; Cancer survivors; Disease surveillance; Epìdemiology; Health-related quality of life; Patient-reported outcome measures; Study protocol; Unmet needs